ANALISIS PERTUMBUHAN TANAMAN REVEGETASI DI LAHAN BEKAS TAMBANG SILIKA HOLCIM EDUCATIONAL FOREST (HEF) CIBADAK, SUKABUMI - Rizki Widiyatmoko; Basuki Wasis; Lilik Budi Prasetyo (Graduate School Bogor Agricultural University (SPs IPB), 2017)
The activity determines the success of reclamation is revegetation, therefore it is needed to conduct evaluation of revegetation plant growth to identify the success of post mining silica land revegetation in HEF. This research aimed to identify the status of revegetation plant growth in HEF based on spatial analysis and plant condition as well as to provide recommendation to address revegetation problems in Holcim Educational Forest. The method used by making 19 plots size of 25 m x 40 m in 4 planting blocks in HEF and conduct spatial analysis to obtain NDVI value from 2013-2016. Parameters observed were height growth, life percentage, plant health, and soil analysis. The result shows that block XI, XIII, and IX had life percentage around 82.03-86.50 and in block VII had life percentage under 80%, while the plants health in HEF block was under 80%. Spatial analysis in HEF block shows that NDVI value in HEF planting blocks increased with average NDVI 0.10. The problem occurred in HEF planting blocks was low life percentage and plants health caused by nutrient content, low pH, soil compaction, and high toxic content such as Fe, Al, and Mn.